1980
DOI: 10.1139/v80-330
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of singlet oxygen. Part V. Dye sensitized photooxidation of m-hydroxydiphenylamine

Abstract: Methylene blue sensitized photooxidation of m-hydroxydiphenylamine gives N-(3-hydroxyphenyl)-p-benzoquinoneimine as the primary product in acetonitrile–water medium. The experimental results are in good agreement with the theoretical plots calculated on the basis of the reaction undergoing through the participation of [Formula: see text] as well as the excited dye interacting with the substrate. β-Value and rate constant of reactivity of m-hydroxydiphenylamine with singlet oxygen have been calculated. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…During our ongoing studies we were surprised to find that the related bromoamination of O ‐allyl aldoxime ethers 3 afforded the corresponding bromo‐5,6‐dihydro‐4 H ‐1,3‐oxazines 4 in high yields and diastereoselectivities. 1,3‐Oxazines can be found as a core motif in some natural products5 and are highly desirable target structures due to their antibiotic,6 antitumor,7 hepatoprotective,8 and analgesic9 properties. Several synthetic methods have been developed that allow for the preparation of 5,6‐dihydro‐4 H ‐1,3‐oxazines 10.…”
Section: Methodsmentioning
confidence: 99%
“…During our ongoing studies we were surprised to find that the related bromoamination of O ‐allyl aldoxime ethers 3 afforded the corresponding bromo‐5,6‐dihydro‐4 H ‐1,3‐oxazines 4 in high yields and diastereoselectivities. 1,3‐Oxazines can be found as a core motif in some natural products5 and are highly desirable target structures due to their antibiotic,6 antitumor,7 hepatoprotective,8 and analgesic9 properties. Several synthetic methods have been developed that allow for the preparation of 5,6‐dihydro‐4 H ‐1,3‐oxazines 10.…”
Section: Methodsmentioning
confidence: 99%
“…The nitro group of the molecule acts as a strong acceptor to manipulate colour by creating large bathochromic shifts, while N ‐β‐hydroxyethyl increases the hydrophilicity. The products of amine photooxidation are nitroso‐ and nitro‐derivatives and quinones 26–33 …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on simple chemicals have led to rapid advances in the understanding of photosensitized oxidation. Not only one pathway but a number of different pathways have been shown to occur [1,2]. Photosensitized oxidation of amines and other compounds showed that dyes act as a sensitizer in a large number of these reactions [3].…”
Section: Introductionmentioning
confidence: 99%